Agricultural water management and poverty linkages - Namara, Regassa E.; Hanjra, Munir A.; Castillo, G.E.; Ravnborg, Helle Munk; Smith, L.; van Koppen, Barbara (Elsevier, 2010)
Water is critically important to the livelihoods of more than 1 billion people living on less than $1 a day, particularly for the 850 million rural poor primarily engaged in agriculture. In many developing countries, water is a major factor constraining agricultural output, and income of the world's rural poor. Improved agricultural water management can contribute to poverty reduction through several pathways. First, access to reliable water improves production and productivity, enhances employment opportunities and stabilizes income and consumption. Secondly, it encourages the utilization of other yield-enhancing inputs and allows diversification into high-value products, enhances nonfarm outputs and employment, and fulfills multiple needs of households. Third, it may contribute either negatively or positively to nutritional status, health, societal equity and environment. The net impact of agricultural water management interventions on poverty may depend individually and/or synergistically on the working of these pathways. Improved access to water is essential, but not sufficient for sustained poverty reduction. Investments are needed in agricultural science and technology, policies and institutions, economic reform, addressing global agricultural trade inequities, etc. But how best to match the agricultural water management technologies, institutions and policies to the needs of the heterogeneous poor living in diverse agro-ecological settings remains unclear. This article provides a menu of promising pathways through which agricultural water management can contribute to sustained poverty reduction.